FRI0494 RHEUMATIC IMMUNE RELATED ADVERSE EVENTS OF CHECKPOINT INHIBITORS: A RETROSPECTIVE REVIEW OF 70 PATIENTS. (2nd June 2020) - Lenfant, T.; Calabrese, L.; Calabrese, C.
Abstract : Background: Immune Checkpoint inhibitors (ICI) have revolutionized cancer therapy by achieving remarkable survival benefits however, at the cost of a myriad of immune-related adverse events (irAEs)[1]. Rheumatic irAE can develop in 5-10% of patients although the true incidence is unknown given the lack of prospective studies [2]. Symptoms are heterogenous and probably underreported with few data available about their management and outcome [3]. Objectives: To describe the clinical, biological, and radiological features of the largest cohort of rheumatic irAEs from ICI along with their therapeutic management, outcome and follow-up in real-world practice. Methods: A referral process for emergent rheumatic irAEs was initiated in February 2016 between the oncology and rheumatology departments at the Cleveland Clinic Foundation. All patients were evaluated by authors CC and/or LHC. Patients' characteristics were retrospectively collected from medical charts after IRB approval. Results: 70 patients referred for one or more rheumatic irAEs between February 2016 and January 2020 were included. 66% were male, median age was 60.8 years. Among them, 24 (34%) had pre-existing rheumatic complaints. Melanoma was the most frequent malignancy (56%). ICI therapy included anti-CTLA4 (40%), anti-PD1/L1 (79%), and dual therapy ipilimumab/nivolumab (41%). Rheumatic irAE occurred in a median 4 months after ICI initiation, with phenotypes including inflammatory arthritis (32 patients), sicca-like symptoms (12), polymyalgia rheumatica-like (7), and myositis (2). Oral, intravenous or intraarticular glucocorticoids (GC) were administered to 54 patients (77%). Of these 54 patients, 22 (41%) required long term GC, 19 had bone density scan and 15 received pneumocystis (PJP) prophylaxis. One PJP case, 1 osteoporotic fracture and 2 avascular necrosis cases were reported. 16 patients received conventional DMARDS (23%) and 9 received biologics (13%). ICI therapy was held for rheumatic irAE in 31% of cases and for another systemic irAE in 29%. Median follow-up was 13.6 months, at end of follow-up 51 patients were still on treatment for rheumatic irAE and 41% of them were still symptomatic despite ongoing treatment. Conclusion: Rheumatic irAEs are heterogeneous and often chronic requiring prolonged immunomodulatory therapy. Prospective studies are required to define optimal management of rheumatic irAEs that maintain long-term oncologic outcomes. References: [1]Suarez-Almazor ME, Kim ST, Abdel-Wahab N, Diab A. Review: Immune-Related Adverse Events With Use of Checkpoint Inhibitors for Immunotherapy of Cancer. Arthritis Rheumatol 2017;69:687–99. https://doi.org/10.1002/art.40043 . [2]Abdel-Wahab N, Suarez-Almazor ME. Frequency and distribution of various rheumatic disorders associated with checkpoint inhibitor therapy. Rheumatol (United Kingdom) 2019;58:vii40–8. https://doi.org/10.1093/rheumatology/kez297 . [3]Kostine M, Rouxel L, Barnetche T, Veillon R, Martin F, Dutriaux C, et al. Rheumatic disorders associated with immune checkpoint inhibitors in patients with cancer-clinical aspects and relationship with tumour response: a single-centre prospective cohort study. Ann Rheum Dis 2018;77:393–8. https://doi.org/10.1136/annrheumdis-2017-212257 . Disclosure of Interests: Tiphaine Lenfant: None declared, Leonard Calabrese Consultant of: AbbVie, GSK, Bristol-Myers Squibb, Genentech, Janssen, Novartis, Sanofi, Horizon, Crescendo, and Gilead, Speakers bureau: Sanofi, Horizon, Crescendo, Novartis, Genentech, Janssen, and AbbVie, cassandra calabrese Consultant of: Abbvie GSK, Speakers bureau: Sanofi-Genzyme